Triazatriangulenium-based porous organic polymers for carbon dioxide capture. Issue 109 (21st October 2015) - Hu, Xin-Ming; Chen, Qi; Sui, Zhu-Yin; Zhao, Zhi-Qiang; Bovet, Nicolas; Laursen, Bo W.; Han, Bao-Hang
Abstract : Reversible and preferred adsorption for CO2 is visible spectroscopically on triazatriangulenium-based cationic porous organic polymers. Abstract : Porous organic polymers from triazatriangulenium salts (TAPOPs) were developed via oxidative polymerization. FeCl3 -caused chlorination on the triazatriangulenium core was observed, which has a pronounced impact on the photophysical properties and porosity of the polymers. Optimization of reaction conditions affords TAPOPs with a Brunauer–Emmett–Teller specific surface area as high as 940 m 2 g −1 and a carbon dioxide uptake capacity up to 15.4 wt% at 273 K and 1.0 bar. Furthermore, the reversible and preferred adsorption of TAPOPs toward carbon dioxide over nitrogen is not only demonstrated by gas sorption experiments but also gas–sorbent interaction measurements through recording the emission change of TAPOPs under different gas atmospheres using fluorescence microscopy.